Effects of performance deterioration on gas path measurements in an industrial gas turbine - Amare, D.F. (Asian Research Publishing Network, 2016)
Studying gas turbine degradation causes and their consequences helps to obtain profound comprehension in how performance deterioration affects the dependent parameters and to explore relevant information about the nature of the fault signatures for fault diagnostics purpose. In this paper, the effects of compressor fouling, gas generator turbine erosion, and power turbine erosion on the engine dependent parameters were considered separately and together. In this regard, firstly, performance prediction model was developed to LM2500 engine using gas turbine simulation program. It was then used to simulate the deterioration effects by means of artificially implanted fault case patterns. Comparison of the clean and deteriorated measurement gives the deviation due to performance degradation. Accordingly, sensitivity order of the gas path parameters to the corresponding performance deterioration was assessed. This helps to select the key parameters, which are crucial in the process of fault detection and isolation. The results showed that, in most of the cases, air mass flow rate, compressor delivery pressure and temperature, gas generator rotational speed, power turbine inlet pressure, and exhaust gas temperature showed significant deviations. Particularly, the compressor delivery pressure and exhaust gas temperature were the parameters highly influenced by all the fault cases. Moreover, faults that have similar impacts are identified, in order to show the difficulty of gas turbine health assessment through direct observation to the measurement deviations. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.